OsNRAMP3 is a vascular bundles-specific manganese transporter that is responsible for manganese distribution in rice. - Meng Yang (Public Library of Science (PLoS), 2013)
Manganese (Mn) is an essential trace element for plants. Recently, the genes responsible for uptake of Mn in plants were identified in Arabidopsis and rice. However, the mechanism of Mn distribution in plants has not been clarified. In the present study we identified a natural resistance-associated macrophage protein (NRAMP) family gene in rice, OsNRAMP3, involved in Mn distribution. OsNRAMP3 encodes a plasma membrane-localized protein and was specifically expressed in vascular bundles, especially in phloem cells. Yeast complementation assay showed that OsNRAMP3 is a functional Mn-influx transporter. When OsNRAMP3 was absent, rice plants showed high sensitivity to Mn deficiency. Serious necrosis appeared on young leaves and root tips of the OsNRAMP3 knockout line cultivated under low Mn conditions, and high Mn supplies could rescue this phenotype. However, the necrotic young leaves of the knockout line possessed similar levels of Mn to the wild type, suggesting that the necrotic appearance was caused by disturbed distribution of Mn but not a general Mn shortage. Additionally, compared with wild type, leaf Mn content in osnramp3 plants was mostly in older leaves. We conclude that OsNRAMP3 is a vascular bundle-localized Mn-influx transporter involved in Mn distribution and contributes to remobilization of Mn from old to young leaves.